Effect of Aerobic Exercise in Water on Serum Estrogen and C - Reactive Protein and Body Mass Index Level in Obese and Normal Weight Postmenopausal Women - Ketabipoor, Sayyede Marzieh; Koushkie Jahromi, Maryam (Women's health bulletin, 2015)
Background: Menopause is associated with increasing incidence of cardiovascular disease, and different exercise regimens can variously affect different cardiovascular risk factors. Objectives: The aim of this study was to investigate the effect of an aerobic exercise in water on serum estrogen, C-reactive protein (CRP) and body mass index (BMI) levels in obese and normal weight postmenopausal women. Patients and Methods: This quasi-experimental study comprised 29 volunteer non-athletic postmenopausal women with mean age 57.04 ± 4.68 years. The study subjects were divided into two groups of obese (n = 15; BMI = 30.21 ± 3.89) and normal weight (n = 14; BMI = 22.43 ± 2.45) according to their BMI. The subjects of both groups participated in aquatic exercise training for 8 weeks, 3 sessions a week, with progressive intensity of 50 to 70 percent of maximum heart rate for 45 minutes between 10-11 am. The blood samples were taken the day before and two days after the exercise sessions through the left brachial vein. Wilcoxon signed ranks test and Mann-Whitney test were used for data analysis. Results: In the obese and normal weight groups exercise caused significant increase in estrogen (P=0.001, P = 0.001, respectively) and decreased the BMI (P = 0.009, P = 0.003, respectively); however, CRP decreased significantly when compared to pre exercise in the normal weight group (P = 0.005), No statistically significant change was observed in the obese group (P = 0.084). There was no significant difference in estrogen (P = 0.32), BMI (P = 0.62) and CRP (P = 0.35) changes following exercise between obese and normal weight groups. Conclusions: In the present study, aquatic aerobic exercise caused similar reduction in some cardiovascular risk factors among obese and normal weight postmenopausal women. However, future studies are recommended for more clarification.